Análise dos efeitos econômicos da Lei 12.485/11 no mercado audiovisual - Santos, Fernando Jacinto Anhê [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Após seis anos de aprovação da Lei 12.485/11 (Lei da TV Paga) é possível notar seus efeitos econômicos no mercado audiovisual. A legislação dispõe de artigos que determinam política de cotas para vários elos da cadeia produtiva do audiovisual. A lei também destina verbas provenientes da cobrança do CONDECINE ao FSA (Fundo Setorial do Audiovisual), que é responsável por fomentar e financiar o mercado audiovisual brasileiro. Esta pesquisa tem como objetivo principal observar os efeitos econômicos da lei 12.485/11 no mercado audiovisual nacional em diferentes elos de sua cadeia produtiva. Para isso, a pesquisa começa com um resgate histórico sobre a economia política nacional, sobre seus aspectos legais, políticos e econômicos; sintetiza os primeiros decretos para regular a radiodifusão do governo de Vargas, os decretos de Jânio Quadros, o desenvolvimento da pioneira Lei do Cabo e o desenvolvimento e implementação da Lei 12.485/11. O estudo também faz menção ao período que vai do fim do Império até a década de 1930, quando o modelo agrário e escravagista vai sendo substituído pelas atividades fabris e comerciais. Para estudar os efeitos da Lei 12.485/11 no mercado audiovisual a pesquisa busca observar o contexto histórico, para depois observar os dados qualitativos e quantitativos disponibilizados por diversas entidades sobre os efeitos da Lei 12.485/11 no mercado audiovisual. Em um segundo momento, a pesquisa traz dados relacionados a todos os elos da cadeia produtiva do audiovisual, geração de empregos, novas empresas, novas formas de captar recursos, disponibilizados por entidades do setor. Ao final, o projeto analisa os efeitos econômicos da Lei 12.485/11 a partir dos dados apresentados pela pesquisa e também utiliza a opinião de profissionais atuantes no setor audiovisual para traçar um panorama do mercado audiovisual após a Lei 12.485/11.

This project presents the current economic participation of the Brazilian audiovisual sector and investigates the modes of production, forms of distribution, circulation and consumption of audiovisual products in various media and broadcasting platforms. The research shows the history of industry problems such as economic underdevelopment, the concentration of capital in some productive poles in a few regions of the country, the lack of regulation of activities, job insecurity in the area and the lack of economic planning of the State for the strategic development of audiovisual production. Also carry on about Brazilian economic crises of 1962, 1974 and 1981 to explain the current economic crisis which also affects the Brazilian symbolic economy. The second part of the project evaluates the economic effects and professionals of Law 12,845, law the "pay TV" in the fundraising market for audiovisual projects and analyzes the data provided by the market, to make economic projections for the sector due to the current national economic scenario. The project also assesses whether the Law 12,845 could actually achieve its goals of promoting new local and regional content developers, or are just going relocation of professional structures of the major producers. After all, there is the possibility of them have moved to occupy new market niches opened by mandatory regionalization of the pay television programming. The third part of the project brings the implementation of management methodology Project Management Institute projects (PMI) to raise funds for audiovisual projects with the Sector Fund Audiovisual (FSA). The methodology in question includes the planning scope, time, cost, quality, human resources, communications, risk, procurement and project stakeholders. The methodological procedures using various tools and dynamics necessary to obtain information for the development projects. The work aims to assess the economic effects of Law 12,845 in the Brazilian audiovisual market and see the different ways to raise funds open by law. The survey also performs the analysis of economic history and regulation of communications in the country, in order to clarify the current situation. After the prospect of realistically economic political scenario, the graduate student applies to the PMI project management methodology, directing the project to its most practical dimension.
Analysis of the economic effects of Law 12.485/11 on the audiovisual market
Keywords: Economia política da comunicação; Lei da TV Paga; Financiamento de projetos; Regulamentação da produção audiovisual; Political economy of communication; Law of cable TV; Project finance; Regulation of audiovisual production